2011
DOI: 10.1016/j.apsusc.2011.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Stability of phosphonic self assembled monolayers (SAMs) on cobalt chromium (Co–Cr) alloy under oxidative conditions

Abstract: Cobalt Chromium (Co-Cr) alloys has been widely used in the biomedical arena for cardiovascular, orthopedic and dental applications. Surface modification of the alloy allows us to tailor the interfacial properties to address critical challenges of Co-Cr alloy in medical applications. Self assembled monolayers (SAMs) of Octadecylphosphonic acid (ODPA) have been used to form thin films on the oxide layer of the Co-Cr alloy surface by solution deposition technique. The SAMs formed were investigated for their stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 55 publications
3
31
0
Order By: Relevance
“…The chemisorption of carboxylic acids on the native oxide surfaces of many metals including magnesium and its alloys yields stable SAMs in a simple immersion process [13,[16][17][18][19]. Phosphonic acid SAMs have also been reported on the native oxide surfaces on many metals and alloys such as aluminum [20][21][22][23], copper [24,25], nickel [26], iron [27], titanium [23,28,29], steel [30,31], nitinol [31,32], cobalt-chromium [33] and so on. The preparation of alkylphosphonic acid SAMs on magnesium alloys by vapor deposition and simple immersion methods has been reported recently by Ishizaki et al [34,35].…”
Section: Introductionmentioning
confidence: 95%
“…The chemisorption of carboxylic acids on the native oxide surfaces of many metals including magnesium and its alloys yields stable SAMs in a simple immersion process [13,[16][17][18][19]. Phosphonic acid SAMs have also been reported on the native oxide surfaces on many metals and alloys such as aluminum [20][21][22][23], copper [24,25], nickel [26], iron [27], titanium [23,28,29], steel [30,31], nitinol [31,32], cobalt-chromium [33] and so on. The preparation of alkylphosphonic acid SAMs on magnesium alloys by vapor deposition and simple immersion methods has been reported recently by Ishizaki et al [34,35].…”
Section: Introductionmentioning
confidence: 95%
“…Samples of the alloy modified in this way were tested for resistance to oxidizing conditions in a laboratory medium and in phosphate buffer solution (PBS) with a pH of 7.4 for 1 to 14 days, and then studied by XPS, AFM and measurements. The stability of the SAM and the hydrophobicity of the alloy surface throughout the study were confirmed [101,103].…”
Section: Mono-and Diphosphonic Acids and Their Saltsmentioning
confidence: 64%
“…Although it has not been possible to find reports on the formation of SAMs upon adsorption of APhs on Co itself, studies of this kind are widely known for Co-Cr alloys [100][101][102][103]. These alloys are widely used in cardiovascular stents, orthopedics and dentistry.…”
Section: Mono-and Diphosphonic Acids and Their Saltsmentioning
confidence: 99%
“…The O 1s emission peaks were deconvoluted using four Voight curves with BEs of 530.9 eV, 531.8 eV, 532.9 eV, and 533.9 eV, which can be attributed to the oxide ions (O 2− ), mainly MgO [34,38,39], phosphonate oxygen bonded to the metal (P-O-M) [30,[37][38][39][40][41], P-OH group [38][39][40]42], and P=O group [39,40]. A dominant peak attributed to phosphonate oxygen bonded to the metal (P-O-M) [30,[37][38][39][40][41] has been attributed to metallic hydroxide by Ishizaki et al, and a few other authors have attributed it to the P=O bond [30,37,39,41] as well as phosphonate oxygen-metal bond. The presence of P-OH groups can contribute to cross-link stabilization of the SAM by allowing hydrogen bond interactions between adhesive groups.…”
Section: Optimization Of the Pretreatment Parameters For The Formatiomentioning
confidence: 99%